Production of experimental aneurysms at a surgically created arterial bifurcation. - Forrest, M D; O'Reilly, G V (American Journal of Neuroradiology, 1989)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf